A review of microgrid development in the United States – A decade of progress on policies, demonstrations, controls, and software tools. (15th October 2018) - Feng, Wei; Jin, Ming; Liu, Xu; Bao, Yi; Marnay, Chris; Yao, Cheng; Yu, Jiancheng
Highlights: Conduct comprehensive literature review of U.S. microgrid development in the recent decade. Discuss U.S. progress on microgrid policies, demonstration projects, control methods, and software tools. Summarize key successful experience of U.S. microgrid development. Abstract: Microgrids have become increasingly popular in the United States. Supported by favorable federal and local policies, microgrid projects can provide greater energy stability and resilience within a project site or community. This paper reviews major federal, state, and utility-level policies driving microgrid development in the United States. Representative U.S. demonstration projects are selected and their technical characteristics and non-technical features are introduced. The paper discusses trends in the technology development of microgrid systems as well as microgrid control methods and interactions within the electricity market. Software tools for microgrid design, planning, and performance analysis are illustrated with each tool's core capability. Finally, the paper summarizes the successes and lessons learned during the recent expansion of the U.S. microgrid industry that may serve as a reference for other countries developing their own microgrid industries.